The effects of psychological capital and job satisfaction on work engagement of support staff at a holdings establishment (Meridian Holdings) - Ramsden, Kelly-Anne (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.